God, sexuality and the self: an essay 'on the Trinity' - Coakley, Sarah (Cambridge University Press, 2013)
God, Sexuality and the Self is a new venture in systematic theology. Sarah Coakley invites the reader to re-conceive the relation of sexual desire and the desire for God and - through the lens of prayer practice - to chart the intrinsic connection of this relation to a theology of the Trinity. The goal is to integrate the demanding ascetical undertaking of prayer with the recovery of lost and neglected materials from the tradition and thus to reanimate doctrinal reflection both imaginatively and spiritually. What emerges is a vision of human longing for the triune God which is both edgy and compelling: Coakley's théologie totale questions standard shibboleths on 'sexuality' and 'gender' and thereby suggests a way beyond current destructive impasses in the churches. The book is clearly and accessibly written and will be of great interest to all scholars and students of theology.